PENGARUH PEMBERIAN INSEKTISIDA DIAZINON DENGAN DOSIS YANG BERBEDA TERHADAP DAYA TETAS DAN ABNORMALITAS PADA LARVA IKAN MAS (Cyprinus carpio) - Yani, Darmiati; Ibrahim, Yusran; Diana, Farah; Zulfadhli, Zulfadhli; Salim, Mahyuddin (JURNAL AKUAKULTURA, 2022)
This study aimed to examine the effect of the insecticide diazinon on the hatchability of fish eggs. The research method used a completely randomized design method which included 4 treatments with 3 replications, namely P0 (control) P1 (0.4 ml/L), P2 (0.35 ml/L), and P3 (0.3 ml/L). The test parameters included fecundity, egg hatchability, larval abnormalities, and water quality. The results showed that the highest fecundity in this study contained 10,357 items. The highest egg hatchability was found in treatment P3 with 0.3% higher concentration (79%) and treatment P2 had hatchability values (57%), P1 (40%) and P0 (44%). The highest abnormality was found in the P0 treatment (control), which was 0.03%. While the water quality at the time of the study was still tolerable by fish larvae.